Village Marketing Development Model Through Local Resources to Alleviate Poverty in Benjeng Gresik Village - Kartika, Chandra; Indrawati, Mei; Zulfikar, Mochamad; Sri Lestari, Veronika Nugraheni (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2024)
Marketing Village Development Model Through Local Resources to Alleviate Poverty in Benjeng Village, Gresik Regency. This research aims to test and analyze the Marketing Village Development Model through Local Resources to Alleviate Poverty in Benjeng Gresik Village. The sample in the research was 15 correspondents who were related to local resources. The sampling method used in this research was to take respondents who were interested in developing existing resources in Benjeng Gresik Village. The data collection method was carried out by distributing interviews to correspondents related to the research, namely respondents in Benjeng Village, Gresik Regency. The data analysis technique is PLC. strategy analysis. The research results from this research activity provide positive results in increasing contributions to improving the economy through developing marketing villages and local resources that can improve the welfare of the people of Benjeng Village, Gresik Regency.